The effects of amphibian population declines on the structure and function of Neotropical stream ecosystems. Issue 1 (1st February 2006) - Whiles, Matt R.; Lips, Karen R.; Pringle, Cathy M.; Kilham, Susan S.; Bixby, Rebecca J.; Brenes, Roberto; Connelly, Scott; Colon-Gaud, Jose Checo; Hunte-Brown, Meshagae; Huryn, Alexander D.; Montgomery, Chad; Peterson, Scot
Abstract : Amphibians can be important consumers in both aquatic and terrestrial habitats and may represent an important energetic link between the two, particularly in the tropics, where amphibian species richness and abundance are high. In the past 20 years, amphibian populations have declined dramatically around the world; numbers have decreased catastrophically in protected upland sites throughout the neotropics, usually resulting in the disappearance of over 75% of amphibians at a given site, particularly those species that breed in streams. Most studies of amphibian declines have focused on identifying causes and documenting changes in adult abundance, rather than on their ecological consequences. Here, we review evidence for the potential ecological effects of catastrophic amphibian declines, focusing on neotropical highland streams, where impacts will likely be greatest. Evidence to date suggests that amphibian declines will have large‐scale and lasting ecosystem‐level effects, including changes in algal community structure and primary production, altered organic matter dynamics, changes in other consumers such as aquatic insects and riparian predators, and reduced energy transfers between streams and riparian habitats. Furthermore, because of habitat and functional differences between larvae and adults in most amphibians, the loss of a single species is akin to losing two species.